2014
DOI: 10.1242/dev.099747
|View full text |Cite
|
Sign up to set email alerts
|

Fgf10-positive cells represent a progenitor cell population during lung development and postnatally

Abstract: The lung mesenchyme consists of a widely heterogeneous population of cells that play crucial roles during development and homeostasis after birth. These cells belong to myogenic, adipogenic, chondrogenic, neuronal and other lineages. Yet, no clear hierarchy for these lineages has been established. We have previously generated a novel Fgf10 iCre knock-in mouse line that allows lineage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
147
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 46 publications
16
147
1
Order By: Relevance
“…FGF10 is also involved in white adipose tissue formation by activating the PPARγ pathway (Asaki et al, 2004;Sakaue et al, 2002) and our group has shown that Fgf10 expression identifies a subset of lipofibroblast progenitors during embryonic development (El Agha et al, 2014). In this study, we show that FGF10 + cells contribute to the activated myofibroblast population in the mouse model of lung fibrosis and that they acquire lipofibroblast characteristics in the resolution phase.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…FGF10 is also involved in white adipose tissue formation by activating the PPARγ pathway (Asaki et al, 2004;Sakaue et al, 2002) and our group has shown that Fgf10 expression identifies a subset of lipofibroblast progenitors during embryonic development (El Agha et al, 2014). In this study, we show that FGF10 + cells contribute to the activated myofibroblast population in the mouse model of lung fibrosis and that they acquire lipofibroblast characteristics in the resolution phase.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, lipofibroblasts isolated from neonatal rat lungs transdifferentiate to myofibroblasts in response to hyperoxia (Rehan and Torday, 2003) or nicotine exposure (Rehan et al, 2005) in vitro. In a previous study, our group has shown that lipofibroblasts trace back to at least one embryonic population of mesenchymal cells expressing fibroblast growth factor 10 (Fgf10) (El Agha et al, 2014). FGF10 is a potent morphogen that plays a key role in lung organogenesis as demonstrated by Fgf10 knockout mice that suffer from lung agenesis (Bellusci et al, 1997;Sekine et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we used Fgf10-lacZ mice to show that during early embryonic lung development (E12.5-E13.5) expression of Fgf10 identifies airway smooth muscle cell progenitors (Mailleux et al, 2005). More recently, using Fgf10 iCre knock-in mice, we showed that during late pseudoglandular and early saccular stages (E15.5-E18.5) Fgf10 is predominantly expressed in cells of the lung parenchyma compared with the airway smooth muscle cells, and these cells are mostly identified as LIFs (El Agha et al, 2014). Here, we provide evidence that Fgf10 plays a functional role in LIF formation.…”
Section: Discussionmentioning
confidence: 94%
“…Following intraperitoneal (IP) injection of tamoxifen into Fgf10 iCre/+ ;tomato flox/+ mice at E11.5 or E15.5, ∼30 and 40% of labeled cells, respectively, trace to Adrp + LIFs when quantified at E18.5 (El Agha et al, 2014). In the present study, IP injection of tamoxifen was carried out twice, at E11.5 and E14.5, in order to maximize the labeling of LIFs derived from Fgf10 + cells (Fig.…”
Section: Lipofibroblast Formation Increases Progressively During Embrmentioning
confidence: 90%
See 1 more Smart Citation